The Bioarchaeological Analysis of Human and Animal Remains: Early Medieval Graves from Vinkovci (Croatia) - Hincak, Zdravka (Array, 2014)
A rescue archaeological excavation on archaeological site „Photo“ (Passage A. Ullman 1A) in town Vinkovci was conducted by an archaeological team of Vinkovci Municipal Museum during 1993. Some of the finds and layers were dated in the Late Roman period (5th-6th century). Although baroque constructions devastated Roman period cultural layers, a part of a public Roman object, a part of a town street – decumanus – and a part of a main collector – cloaca – beneath were explored, all dated to 2nd and 3rd century. In the site ten graves with inhumation burial rite, four with enclosed grave goods and three pits with skeletal human remains were revealed. The graves were dug in the Late Roman layer of construction waste, beside the remains of the antique walls, and one was placed directly on decumanus. The burials are primary, with orientation West-East and a slight deviation from South. Sex and age at death determination was made on all remains of adult persons. For all infant skeletons age was determined, while sex was supposed only for better preserved skeletons. Pathological changes visible on the bone and dental material were observed. This study aims to present potentials of joined classical anthropological and histological analysis on less preserved bone material. In some graves animal osteological material was found. Mostly fragmented long bone samples which were also analysed by histological method.